Mathematical simulation of composite ingots crystallisation - V. I. Bolotov; V. S. Minaeva; I. A. Pavljuchenkov; A. P. Stovpchenko (Литьë и металлургия)
The results are presented of mathematical simulation of forming of composite ingots with different formula and properties of external and internal levels. Limit parameters of solid plug thickness are determined